Vehicles for atopic dermatitis therapies: more than just a placebo. (17th February 2022) - Danby, Simon G.; Draelos, Zoe D.; Gold, Linda F. Stein; Cha, Amy; Vlahos, Bonnie; Aikman, Laraine; Sanders, Paul; Wu-Linhares, Dan; Cork, Michael J.
Abstract: A topical vehicle is a 'carrier system' for an active pharmaceutical (or cosmetic) substance, referred to hereafter as the drug, but a vehicle may also be used on its own as an emollient to ameliorate dry skin. It is well established that the vehicle plays an important role in determining the bioavailability of a given drug at its ultimate target within the skin. Yet in the treatment of atopic eczema/dermatitis (AD), wherein the structure and function of the skin's outer barrier play a pivotal role in the development and course of the condition, the interaction of the vehicle with this barrier carries a particular importance. It is now clear that the often-considered inert excipients of a vehicle bring about changes within the skin at the molecular level that promote barrier restoration and enhance innate immune defenses with therapeutic value to AD patients. Moreover, the vehicle control in randomized controlled trials (RCTs) increasingly displays significant efficacy. In light of this, we consider the implications of vehicle design in relation to AD pathophysiology and the role vehicles play as controls in RCTs of new drug treatments for this condition.